ELEMENTARY SCHOOL TEACHERS’ PERCEPTION OF INCLUSIVE EDUCATION IN EAST JAVA, INDONESIA - Junaidi, Ahsan R; Sunandar, Asep; Yuwono, Joko; Ediyanto, Ediyanto (International Journal of Educational Management and Innovation, 2021)
Teachers' perception of inclusive education becomes an important indicator in evaluating the success of inclusive education. Teachers who have a positive perception of inclusive education will have a more controlled learning environment. This study used a survey method that investigates the current views of elementary school teachers toward inclusive education by exploring their perceptions. The respondents of this study are 70 elementary school teachers in East Java Province. This study found that: (1) There was no difference perception of teachers in primary schools concerning the concept of inclusive education, placement of students with disabilities, and processing of learning in inclusive classrooms; (2) Teachers' perceptions in primary schools towards inclusive education was not influenced by their duties as regular and special education teachers; (3) There are differences in perceptions of inclusive education based on the amount of training they followed; (4) There are differences in teachers' perceptions of inclusive education based on the length of teachers' experience teaching students with disabilities. Teachers' perceptions of inclusive education can be measured from three dimensions: the inclusion concept, disability student placement, and learning management.